2012
DOI: 10.1017/s0030605311001402
|View full text |Cite
|
Sign up to set email alerts
|

Trends in extinction and persistence of diurnal primates in the fragmented lowland rainforests of the Upper Brahmaputra Valley, north-eastern India

Abstract: The historical deforestation of the Upper Brahmaputra Valley in the Indian state of Assam has resulted in the transformation of its once-contiguous lowland rainforests into many isolated forest fragments that are still rich in species, including primates. We report the recent history and current status of six diurnal primates in one large (2,098 ha) and three small (, 500 ha) fragments of the Upper Brahmaputra Valley. We censused primates in the small fragments during 2002, 2005, 2009, in the large fragment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…As gibbons are known to prefer dense or pristine forest for living, it is a major concern for conservationist to protect dense forest areas. The shrinkage of forest cover areas in fragments of known gibbon habitats in the study area has also been reported in earlier studies (Kakati 2004, Sharma et al 2012a, Sharma et al 2013) due to which the population is eventually exposed to open forest. Therefore, in the present study, the predictive potential habitat of the species is used as a primary tool to compare the habitat of the species on a temporal scale with particular reference to forest covers and canopy covers.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As gibbons are known to prefer dense or pristine forest for living, it is a major concern for conservationist to protect dense forest areas. The shrinkage of forest cover areas in fragments of known gibbon habitats in the study area has also been reported in earlier studies (Kakati 2004, Sharma et al 2012a, Sharma et al 2013) due to which the population is eventually exposed to open forest. Therefore, in the present study, the predictive potential habitat of the species is used as a primary tool to compare the habitat of the species on a temporal scale with particular reference to forest covers and canopy covers.…”
Section: Discussionsupporting
confidence: 85%
“…The same argument was also supported by Sarma et al (2015) in the predictive distribution of eastern hoolock gibbon in Arunachal Pradesh, India. Moreover, extirpation of gibbons and other coexisting primates from several small fragments of the Upper Brahmaputra Valley (Kakati 2004, Sharma et al 2012aand 2012b, Sharma et al 2013) demand the study of localized speci c habitat needs of the primates in general.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not directly address movement of species through the matrix, we believe that persistence of the capped langur and Assamese macaque in certain fragments may have been unaffected by the matrix because these 2 species sometimes use the vegetation in these areas and the capped langur, on occasion, colonizes new forest fragments by moving across the matrix (Sharma et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important variable affecting stump‐tailed macaque distribution was forested area. Given its large home range (400–900 ha in one fragment, the Hollongapar Gibbon Wildlife Sanctuary [Sharma et al ]), smaller fragments may not support populations of this species, as has been reported for other wide‐ranging Neotropical primates (Schwarzkopf & Rylands ).…”
Section: Discussionmentioning
confidence: 99%
“…Primates, especially macaques, present interesting case studies, as they are extremely ecologically adaptable and capable of co-existing and interacting with humans at rather close quarters. What is often not recognised, however, is that some of these so-called adaptable macaques are now becoming locally extinct [ 43 , 44 ] and even the common species may have begun to slowly disappear from their well-known, and thus often neglected, habitats [ 9 , 45 , 46 ]. Changes in the demography and behavioural ecology of newly threatened populations of these species, therefore, can be overlooked and fail to garner crucial conservation attention [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%